Evaluasi Kinerja Instalasi Pengolahan Air Limbah (IPAL) di PT. Rohul Sawit Industri - Yasmin Nabilah; Putri, Tanti Nabella; Widiasa, I Nyoman; Tito, Adryan; Adyaksa, M. Nur (Talenta Publisher (Universitas Sumatera Utara), 2022)
This paper reports the performance evaluation results of the wastewater treatment plant and the quality of the effluent from the palm oil mill of PT. Rohul Sawit Industri in 2021, which uses Ponding System methods. PT. Rohul Sawit Industri are allowed to reuse the results of their waste treatment into the Land Application System. The faculative waste is monitored once a month where the data is in accordance with the UKL–UPL matrix. In the liquid waste test, samples of liquid waste are taken from the last outlet which will be flowed to the study area, referring to the applicable water sampling method. The results of laboratory tests showed that for 6 months the pH was relatively constant between ​​7–8 and the Biological Oxygen Demand (BOD) was always below 5,000 mg/L. Both of these parameters have met the quality standards that have been set in the Decree of the State Minister of the Environment No. 29th in 2003. The level of Chemical Oxygen Demand (COD) in wastewater is between 1912.2 mg/L–9389.67 mg/L, oil and fat content in wastewater is between 6.1 mg/L–15.3 mg/L, Total Suspended Solid (TSS) liquid waste is between 700 mg/L–55,920 mg/L, ammonia levels in palm oil waste are around 62.5 mg/L–215.5 mg/L, Pb levels in waste are between 0 .08 mg/L–0.155 mg/L, Cu levels in waste are always less than 0.005 mg/L, Cd levels in sewage are always less than 0.01 mg/L, and Zn levels in waste are between 0.012 mg/L–0.098 mg/L. Based on this, the processing of liquid waste from the palm oil mill of PT. Rohul Sawit Industri is quite good because the quality of the liquid waste is still below the quality standard.